2013
DOI: 10.1096/fj.13-230433
|View full text |Cite
|
Sign up to set email alerts
|

Exchange protein activated by cAMP 1(Epac1)‐deficient mice develop β‐cell dysfunction and metabolic syndrome

Abstract: Previously, exchange protein directly activated by cAMP 2 (Epac2) and PKA were known to play a role in glucose-stimulated insulin secretion (GSIS) by pancreatic β cells. The present study shows that Epac1 mRNA is also expressed by β cells. Therefore, we generated mice and embryonic stem (ES) cells with deletion of the Epac1 gene to define its role in β-cell biology and metabolism. The homozygous Epac1-knockout (Epac1(-/-)) mice developed impaired glucose tolerance and GSIS with deranged islet cytoarchitecture,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 46 publications
(52 reference statements)
5
47
1
Order By: Relevance
“…The Epac1  mice displayed neither developmental nor reproductive abnormalities, but they showed an impaired glucose tolerance and insulin secretion reduction after glucose challenge when compared with their Epac1 +/+ littermates [20]. Epac2  mice also have such insulin secretion dysfunction after glucose stimulation [26].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The Epac1  mice displayed neither developmental nor reproductive abnormalities, but they showed an impaired glucose tolerance and insulin secretion reduction after glucose challenge when compared with their Epac1 +/+ littermates [20]. Epac2  mice also have such insulin secretion dysfunction after glucose stimulation [26].…”
Section: Discussionmentioning
confidence: 93%
“… mice were generated previously [20], and they were backcrossed to C57BL/6N mice for more than 10 generations. Age-matched Epac1 +/+ littermates served as the control group.…”
Section: Epac1mentioning
confidence: 99%
“…Previous studies reported that the GEFs Epac1 and Epac2 attenuate cellular leptin signaling in cultured cells and brain slices (Fukuda et al, 2011; Sands et al, 2006). However, the biological significance of this effect remains controversial because while one study showed resistance to diet-induced obesity in Epac1-null mice (Yan et al, 2013), another reported augmented diet-induced obesity and glucose imbalance in the Epac1 global-knockout mice (Kai et al, 2013). In contrast to this conflicting data on the role of Epac1 in the control of whole-body energy and glucose balance, our findings suggest that brain Epac2 is likely involved in Rap1 activation and its effects on hypothalamic functions in HFD-induced obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The implication of reduced EPAC1/ Rap1 functions in CF phenotypes needs to be further explored. For example, EPAC1 deficiency is associated with insulin resistance, and could be a factor in the development of CF-related diabetes (41).…”
Section: Discussionmentioning
confidence: 99%